Mise en œuvre opérationnelle d’un projet de compensation carbone de foyers améliorés au Niger - Fanny Joubert; Milena Begovic (VertigO)
The use of traditional cookstove in Niger has serious consequences for the environmental, health and economic development. The carbon offset improved cookstoves project presented here aims to replace these traditional cookstoves with more efficient cookstoves (called Kiva-Hybrid) in order to reduce wood consumption. The implementation of such a project requires a substantial preliminary work to ensure its sustainability: statistical studies, development and performance tests of several cookstoves prototypes, local stakeholder consultation meetings. Following the Gold Standard methodology, this project will not only reduce worldwide greenhouse gases emissions but also improve the local populations’ livelihoods (fight against deforestation, improvement of indoor air quality, savings of money and time collecting woods). Indeed, wood savings are assessed at 1.5 tons/stove/year on average, which leads to 2.79 tCO2e emissions avoided per year and savings of 47 500 FCFA/year/household.